Sasha Beran-Hughes: capstone - Beran-Hughes, Sasha, artist (Colorado State University. Libraries, 2023)
The artist's statement: If I told my teenage self that I would be a graphic designer, I would have rejected the idea immediately. Interested in mediums such as painting and drawing, I had little regard for graphic design. In truth, I didn't have the knowledge about the world of design because I had only been educated on mediums that weren't technology-based. I soon came to realize that design has monumental impacts on the world around us. Graphic design can create a doughnut craving, or help a shampoo brand sell one bottle over its competitors. It influences large numbers of people on very crucial parts of society, politics, culture, and identity. For me, graphic design isn't just a digital process. It starts as sketches on paper and evolves to the screen. I love that it isn't a lonely process either. Publication design in particular has provided me with the qualities I've always hoped for in a profession: friendship, collaboration, and inclusivity. I can work closely with other creatives such as writers, photographers, and other designers in order to create a collective piece of art that best showcases everyone's work to the world. This not only helps me gain different perspectives, but I'm also able to gain expertise in other creative fields. I began as an illustrator, and I still consider that my niche as well as publication design. My illustration style tends to be very detailed with lots of varied values and color. I have become a lot more familiar with simplifying compositions and shapes in order to challenge what I am most comfortable with. Through the last few years, I have grown to love nearly every aspect of design by learning new skills and trying new styles, and I am so thankful for everything this career path has taught me so far.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design